ANALISIS INOVASI KURIKULUM DAN PEMBELAJARAN PADA MADRASAH ALIYAH SWASTA DI KOTA PADANG PANJANG - Asrizallis; M Yemmardotillah (El-Rusyd, 2022)
This study aims to analyze curriculum innovation and learning at private Madrasah Aliyah in Padang Panjang City in an effort to improve the quality of graduates, through madrasa programs in order to develop mental, moral and intellectual as well as improve students' soft skills and hard skills in dealing with life in society and continue on to higher education. Private Madrasah Aliyah needs to continue to make reforms in the education system, even though currently the quality of private Madrasah Aliyah still needs a lot of innovation, so that graduates of private madrasas are able to compete with madrasas or public schools. This research is a descriptive qualitative research, data obtained through observation, interviews and documentation. The results of research on curriculum innovation and learning at private Madrasah Aliyah in Padang Panjang City include developing curriculum innovation plans, curriculum innovation foundations, curriculum goal innovations that combine madrasah goals and national goals, teaching material innovations and evaluation system development, extracurricular innovations and innovations local content.